2010
DOI: 10.2175/193864710798208421
|View full text |Cite
|
Sign up to set email alerts
|

A New Approach to Nutrient Removal Using the HYBACS Process

Abstract: A major challenge facing the wastewater industry is the production of high quality treated effluents containing reduced concentrations of nutrients. The challenge relates equally to upgrading existing plants as to entirely new construction. The HYBACS process is a new approach to nutrient removal that has been developed from a process originating from South Korea called the RABC process. The process comprises two biological stages followed by clarification (or separation). The first stage comprises SMART units… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 1 publication
0
5
0
Order By: Relevance
“…Two hybrid IFAS-MBR filled with PE carrier media and a filling ratio of 50% were employed in both systems with an HRT of 11.6-14.45 h and 10-20 days SRT to obtain >98% COD removal for both systems [55]. A simultaneous partial nitrification, anammox, and denitrification (SNAD)-IFAS for the ammonium-rich synthetic wastewater with nonwoven polyester rings (density 1.1 g/cm 3 ) was used as the carrier media with a 40% filling ratio and 0.75 d HRT and 20 d SRT employed for 120 days. The effect of pH on the microbial community was investigated, and it was concluded that pH shift affects small changes in microbial community structure [56].…”
Section: Carrier Media Filling Ratiomentioning
confidence: 99%
See 1 more Smart Citation
“…Two hybrid IFAS-MBR filled with PE carrier media and a filling ratio of 50% were employed in both systems with an HRT of 11.6-14.45 h and 10-20 days SRT to obtain >98% COD removal for both systems [55]. A simultaneous partial nitrification, anammox, and denitrification (SNAD)-IFAS for the ammonium-rich synthetic wastewater with nonwoven polyester rings (density 1.1 g/cm 3 ) was used as the carrier media with a 40% filling ratio and 0.75 d HRT and 20 d SRT employed for 120 days. The effect of pH on the microbial community was investigated, and it was concluded that pH shift affects small changes in microbial community structure [56].…”
Section: Carrier Media Filling Ratiomentioning
confidence: 99%
“…Discharge quality, energy efficiency, process cost, nitrogen removal, phosphorous removal, biogas production, and nitrification/denitrification are the key parameters for wastewater treatment. The development of wastewater technology is critical to improving effluent quality, meeting environmental standards, and developing long-term sustainability [ 3 ]. As more restrictive legislation is imposed concerning wastewater treatment, it is inevitable that treatment processes will need to be redesigned to be more efficient, economical, and comply with the limits [ 4 , 5 ].…”
Section: Introductionmentioning
confidence: 99%
“…1d), the conditions in the reactor become increasingly anaerobic which could favour processes that require reduced oxygen levels such as denitrification (Teixeira and Oliveira, 2001). Hybrid systems operate a RBC combined with another unit operation to improve the stability of a process that has strong or variable loading, increase load capacity or improve the achievable effluent standard (Vesilind, 2003;Hoyland et al 2010). Common configurations include a RBC/biofilm (Fig.…”
Section: Typesmentioning
confidence: 99%
“…It accounts for almost 55% of wastewater treatment energy budget. Wastewater treatment technologies can increase removal efficiency of pollutants and more improve effluent quality [3]. Rotating Biological Contactor is an attached growth process in which, microorganisms attached to the media develops a film.…”
Section: Introductionmentioning
confidence: 99%